Sustainable housing development dynamics in the Global South: refl ections on theories, strategies and constraints - Aliu, Ibrahim Rotimi (Bulletin of Geography. Socio-economic Series, 2022)
Background: Sustainability has been on the front burner of global debates in the 21st century because of the three commons: economic development, social equity and environmental stability. Central to the debate on sustainability is housing. Housing, as a fixed, physical structure can undermine development by constituting threats to the physical environment, and housing as an economic commodity can invigorate the process of development by increasing GDP through diverse job creations and revenue generations. However, the intersection of housing development, physical environment and sustainability in the Global South has been under-reported. Aim: The aim of this paper is to contribute to the debate on sustainable housing provision in the Global South based on three valid questions: How can affordable housing be produced for the teeming population, how can sustainable, quality housing be produced, and how can the impacts of housing on the physical environment be regulated? Results and conclusion: The paper discusses housing deficits, sustainable housing development strategies, challenges of sustainable housing provision and potential solutions to sustainable housing development in the Global South region. This paper has useful policy and practical implications for housing development in developing countries.